Commuting time and perceived stress: Evidence from the intra- and inter-city commuting of young workers in Korea. (October 2022) - Jin, Eunae; Kim, Danya; Jin, Jangik
Abstract: Previous studies have revealed that long-duration commuting decreases life satisfaction and increases perceived stress among workers. However, as relatively few studies have examined the relationship between commuting time and overall perceived stress, our understanding of the relationship between the aforementioned variables is limited. Therefore, this study examines the relationship between commuting time and perceived stress by focusing on young Korean workers. For this, we employ a fixed-effects panel data analysis model and collect longitudinal survey data of Korean youth. Our empirical analysis demonstrates that commuting time is negatively associated with young Korean workers' perceived stress. We argue that this may be because young workers are more likely to accept long commuting for higher wages. Findings also show that the relationship between commuting time and perceived stress differs according to commuting patterns (intra- and inter-city commuting) and commuting modes. Particularly, perceived stress is likely to be lower among public transportation users, even though their commuting time is longer, whereas commuters by car experience higher stress as commuting time increases. Our findings suggest that planners should understand workers' heterogeneous preference for commuting and the different spatial characteristics of urban spatial structure that causes long-duration commuting.